Analysis of the Influence of International Trade, Foreign Investment, and Exchange Rates on Economic Growth in 5 Asean Countries from the Perspective of Islamic Economics 2015-2023 - Aditya Dwi Putra; Kurniawan, Muhammad; Is Susanto (Jurnal Internasional Ekonomi Islam, 2025)
Introduction: This study's background is based on the importance of economic stability and growth in the face of changing global dynamics, where regional economic integration is a key factor in determining the region's competitiveness. Objective: This study analyzes the effect of international trade, foreign investment, and the exchange rate on economic growth in the ASEAN region from 2015 to 2023. Method: This study uses a quantitative approach, using panel secondary data obtained from the World Bank and analyzing it through multiple linear regression models using EViews 13 software. Results: The results show that international trade has a significant and positive influence on economic growth in ASEAN countries, signaling its central role in driving regional economic activity. In contrast, foreign investment does not show a significant effect on economic growth over the observed period, indicating that the role of foreign investment is not optimal or may be hampered by structural factors and domestic policies. Meanwhile, the exchange rate shows a positive relationship with economic growth, which may imply that exchange rate stability supports trade and investment activities. Implications: The implications of these findings emphasize the importance of strengthening foreign trade policy and managing a stable exchange rate as key strategies in promoting sustainable economic growth. In the context of Islamic economics, this study also reflects the importance of balance between economic interests and social values, where growth is not only measured in material terms, but should also reflect social justice, welfare, and sustainability.